Beyond hagiography with footnotes writing biographies of the Chabad Rebbe in the post-Schneerson era - Ṭṿoreḳ, Ṿoyṭeḳ 1981- (2019)
This article discusses the biographies of Menachem Mendel Schneerson (the Rebbe) within the broader context of Chabad historiographic lore, in particular the quasi-historical writings of Yosef Yi?ḥak Schneersohn from the 1930s and 1940s. Described by Ada Rapoport-Albert as "hagiography with footnotes," these seemingly scholarly and modern texts constituted an alternative narrative to that of academic Jewish history. From this vantage point, I consider how biographies published by academics and by hasidic authors have mutually influenced each other, particularly in their scope, form, and method. To that end, I examine the controversy that surrounded the 2010 publication of the first academic biography of Schneerson, Samuel Heilman and Menachem Friedman's The Rebbe, and analyze the strategies undertaken by subsequent authors that have allowed them to present the Rebbe's life in a form that was no longer "hagiography with footnotes" (which would have alienated a secular readership) but as seemingly impartial biographies (without alienating the hasidic readership).